Shifting Provider Attitudes and Institutional Resources Surrounding Resuscitation at the Limit of Gestational Viability - Arbour, Kaitlyn; Lindsay, Elizabeth; Laventhal, Naomi; Myers, Patrick; Andrews, Bree; Klar, Angelle; Dunbar, Alston E., III (American Journal of Perinatology, 2020)
Objective This study aimed to provide contemporary data regarding provider perceptions of appropriate care for resuscitation and stabilization of periviable infants and institutional resources available to providers.Study Design A Qualtrics survey was emailed to 672 practicing neonatologists in the United States by use of public databases. Participants were asked about appropriate delivery room care for infants born at 22 to 26 weeks gestational age, factors affecting decision-making, and resources utilized regarding resuscitation. Descriptive statistics were used to analyze the dataset.Results In total, 180 responses were received, and 173 responses analyzed. Regarding preferred course of care based on gestational age, the proportion of respondents endorsing full resuscitation decreased with decreasing gestational age (25 weeks = 99%, 24 = 64%, 23 = 16%, and 22 = 4%). Deference to parental wishes correspondingly increased with decreasing gestational age (25 weeks = 1%, 24 = 35%, 23 = 82%, and 22 = 46%). Provision of comfort care was only endorsed at 22 to 23 weeks (23 weeks = 2%, 22 = 50%). Factors most impacting decision-making at 22 weeks gestational age included: outcomes based on population data (79%), parental wishes (65%), and quality of life measures (63%). Intubation with a 2.5-mm endotracheal tube (84%), surfactant administration in the delivery room (77%), and vascular access (69%) were the most supported therapies for initial stabilization. Availability of institutional resources varied; the most limited were obstetric support for cesarean delivery at the limit of viability (37%), 2.0-mm endotracheal tube (45%), small baby protocols (46%), and a consulting palliative care teams (54%).Conclusion There appears to be discordance in provider attitudes surrounding preferred actions at 23 and 22 weeks. Provider attitudes regarding decision-making at the limit of viability and identified resource limitations are nonuniform. Between-hospital variations in outcomes for periviable infants may be partly attributable to lack of provider consensus and nonuniform resource availability across institutions.Key Points
Keywords: limit of viability; periviable infants; extremely premature infant; provider attitudes; institutional resources